2005
DOI: 10.1007/s00424-005-1468-5
|View full text |Cite
|
Sign up to set email alerts
|

TRPC channels as signal transducers

Abstract: The study of the TRPC cation channels as signal transducers in sensory neurons is in its infancy. Mechanoreceptors that monitor arterial pressure are prime candidates for the involvement of TRPC channels as either primary mechanical transducers or as modulators of the transduction process. Their activity patterns can be regulated by growth factors such as BDNF and by a variety of ligands that activate Gq-coupled receptors, mechanisms that have been shown in heterologous expression systems to activate TRPC chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 27 publications
(30 reference statements)
1
38
0
Order By: Relevance
“…In the NG, TRPC1-C7 expression has been reported in the soma of neurons and only TRPC1 and TRPC3-C5 expression has been observed in fibers in this ganglion (Glazebrook et al, 2005). In the same study, TrpC1 and C3, similar to our observation, exhibited strong staining in neuronal subpopulations with C1, C3, C4, and C5 present in myelinated A-type fibers and C1, C4, and C5 present in nonmyelinated C-type endings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the NG, TRPC1-C7 expression has been reported in the soma of neurons and only TRPC1 and TRPC3-C5 expression has been observed in fibers in this ganglion (Glazebrook et al, 2005). In the same study, TrpC1 and C3, similar to our observation, exhibited strong staining in neuronal subpopulations with C1, C3, C4, and C5 present in myelinated A-type fibers and C1, C4, and C5 present in nonmyelinated C-type endings.…”
Section: Discussionsupporting
confidence: 88%
“…We were interested to examine if expressions of TRPC1-C7 were similar in thoracic DRG as in lumbar ganglia and to see if TRPC channels developmental expression was comparable in another sensory ganglia previously reported to express members of the TRPC family (Glazebrook et al, 2005). Real-time PCR was conducted on the thoracic DRG and NG collected from embryonic, postnatal, and adult stages.…”
Section: Expression Of Trpc Channels In Thoracic Drg and Ngmentioning
confidence: 99%
“…These data indicate that the functions of TRPC channels depend on the specific assembly of TRPC subunits, the tissue type, and the age of animals. TRPC expression in various cell types typically is not limited to a single member but a combination of various TRPC subunits (18,(42)(43)(44). In addition, the TRPC expression profile changes during development.…”
Section: Discussionmentioning
confidence: 99%
“…The results of several studies, chiefly employing immunofluorescence, have identified those cell types in a particular organ in which TRPC1 is expressed. These include neurons (Goel et al 2002;Glazebrook et al 2005;von Bohlen-Und-Halbach et al 2005) the retina (Crousillac et al 2003) and kidney (Goel et al 2006). …”
Section: Expression Of Trpc1 In Tissues and Cellsmentioning
confidence: 98%